Adenosine-mediated immune responses in inflammatory bowel disease - Vuerich, Marta; Nguyen, Du Hanh; Ferrari, Davide; Longhi, Maria Serena (Frontiers in Cell and Developmental Biology, 2024)
Extracellular ATP and its derivates mediate a signaling pathway that might be pharmacologically targeted to treat inflammatory conditions. Extracellular adenosine, the product of ATP hydrolysis by ectonucleotidase enzymes, plays a key role in halting inflammation while promoting immune tolerance. The rate-limiting ectoenzyme ENTPD1/CD39 and the ecto-5′-nucleotidase/CD73 are the prototype members of the ectonucleotidase family, being responsible for ATP degradation into immunosuppressive adenosine. The biological effects of adenosine are mediated via adenosine receptors, a family of G protein-coupled receptors largely expressed on immune cells where they modulate innate and adaptive immune responses.Inflammatory bowel disease (IBD) is a serious inflammatory condition of the gastrointestinal tract, associated with substantial morbidity and often refractory to currently available medications. IBD is linked to altered interactions between the gut microbiota and the immune system in genetically predisposed individuals. A wealth of studies conducted in patients and animal models highlighted the role of various adenosine receptors in the modulation of chronic inflammatory diseases like IBD.In this review, we will discuss the most recent findings on adenosine-mediated immune responses in different cell types, with a focus on IBD and its most common manifestations, Crohn's disease and ulcerative colitis.